King Vajiravudh (Rama VI)’s Encouragement to Thais through His Writing Entitled “Hua Jai Nak Rob - (A Warrior Heart)” - Klaisuwan, Natawut (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
This academic article aims to study of King Vajiravudh (Rama VI)’s encouragement to Thai people through his writing entitled A Warriors Heart (Hua Jai Nak Rob). The findings are as King Vajiravudh (Rama VI) encouraged his people to have an opinion which is concordant with his objectives, i.e. to adore the nation, religion and the King, to be stable in justice and to foresee the terrible end of a person who does not adore the nation. He wished to Thais realize the valuation and necessary of Wild Tiger Corps and Boy Scout.